KONSEP MUSIBAH DALAM TAFSIR AL-IBRIZ KARYA BISRI MUSTOFA - Fahma Maulida; Nyla Uswatun Husniyah (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2025)
The background of the author conducting this research is because calamity is an event that often occurs anywhere and anytime, whether it is due to human action or it is the will of God that cannot be avoided. The purpose of this study is to provide an in-depth discussion of the concept of calamity (musibah) in the Qur’an from the perspective of Tafsir al-Ibriz li Ma‘rifat Tafsir al-Qur’an al-‘Aziz by Bisri Mustofa, as well as to examine the relevance of his interpretations within the context of contemporary life. This research employs a qualitative approach using a library research method for data collection, which involves gathering and analyzing both primary and secondary sources from relevant foundational texts. The results of the data analysis then obtained conclusions, namely, first, calamity is interpreted as a bad event, danger and harm, this is illustrated by Bisri in his interpretation contained in 10 letters. Second, Bisri's interpretation is still relevant to the social context of society in Indonesia today.